Emotion Regulation Diversity in Current and Remitted Depression. (July 2021) - Wen, Alainna; Quigley, Leanne; Yoon, K. Lira; Dobson, Keith S.
Depression is associated with reduced flexibility in emotion regulation (ER). Diversity in the use of ER strategies is crucial for ER flexibility. In this study, we examined associations between depression and ER diversity and proposed a novel measure: the ER diversity index. Currently depressed ( n = 58), remitted depressed ( n = 65), and healthy control participants ( n = 55) rated their use of nine ER strategies. Four ER measures were computed (diversity index, sum score, flexibility score, intraindividual standard deviation), and their association with diagnostic group was compared. The ER diversity index was associated with depression status more strongly than all other ER measures. Currently and remitted depressed individuals exhibited greater diversity in ER strategies overall and maladaptive ER strategies but less diversity in adaptive ER strategies compared with healthy individuals. Thus, the ER diversity index may be a valid measure of ER diversity, and ER diversity may have an important role in depression.